1972
DOI: 10.1116/1.1316577
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in Thin Film Ti–Au, Ti–Pd, and Ti–Pt Couples

Abstract: The interdiffusion and subsequent compound formation was investigated in thin film couples of Ti–Au, Ti–Pd, and Ti–Pt using transmission and glancing angle electron diffraction techniques. Aging temperatures up to 500°C and times up to 8 h were considered. For all three couples, intermetallic compound formation was observed in the as-deposited films indicating substantial diffusion during deposition (= 100–150°C). For the Ti–Au couples, the TiAu2, TiAu, and Ti3Au compounds formed during diffusion. For the Ti-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(70 citation statements)
references
References 0 publications
7
61
0
Order By: Relevance
“…3) showed that the density of threading dislocations (labeled "O" and "A" in Fig. 3) was in the order of 5¥10 SIMS showed that the Pt electrodes on the Ti adhesion layers contained Ti, consistent with findings by others [18][19][20]. The influence of Ti underneath (111) textured Pt electrodes on perovskite film texture is well documented [21,22].…”
Section: A Srtio 3 Thin Film Microstructuresupporting
confidence: 73%
“…3) showed that the density of threading dislocations (labeled "O" and "A" in Fig. 3) was in the order of 5¥10 SIMS showed that the Pt electrodes on the Ti adhesion layers contained Ti, consistent with findings by others [18][19][20]. The influence of Ti underneath (111) textured Pt electrodes on perovskite film texture is well documented [21,22].…”
Section: A Srtio 3 Thin Film Microstructuresupporting
confidence: 73%
“…19 In this study, we did not investigate the possibility of oxidation of the titanium layer through the gate-insulator SiO 2 . The possibility of this oxidation process was excluded through the analysis of V th difference between sensor FETs and reference FETs.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well-known that Ti diffuses through Pt electrodes [18][19][20][21], the precise mechanisms by which Ti underlayers control perovskite thin film textures are not fully understood. In the literature, it has been suggested that either a Pt-Ti intermetallic or TiO 2 on the Pt surface provide a templating layer for (111) epitaxial perovskite growth [14,17].…”
mentioning
confidence: 99%